Youth hedonistic behaviour: moderating role of peer attachment on the effect of religiosity and worldview - Hamzah, Siti Raba'ah; Suandi, Turiman; Krauss, Steven Eric; Hamzah, Azimi; Tamam, Ezhar (Routledge, 2014)
This study was carried out on the moderating effect of peer attachment on the relationships between religiosity and worldview, and on how hedonistic behaviour among Malaysian undergraduate students is shaped by such influences. With regard to peer attachment, the study focused on the influences of communication, trust and alienation among youth. Bronfenbrenner's theory of human ecology and Armsden and Greenberg's attachment model were used as the framework. Drawing on a quantitative survey of 394 Malaysian university students (M age = 21.0, SD = 0.40), structural equation modelling and path analysis revealed a significant relationship between worldview and hedonistic behaviour. Peer attachment moderated the relationships between religiosity and religious worldview. The results further showed that the unique moderating effect of the lower level of attachment with peers is positively related to the hedonistic behaviour. Implications from the findings are discussed.